1991
DOI: 10.1002/aja.1001910311
|View full text |Cite
|
Sign up to set email alerts
|

Sequence‐specific binding of a c‐myc nuclear‐matrix‐associated region shows increased nuclear matrix retention after leukemic cell (HL‐60) differentiation

Abstract: HL-60 cells, a human promyelocytic leukemia cell line, contain amplified c-myc DNA sequences and mRNA transcripts. These cells can be induced to undergo macrophage differentiation by phorbol esters, which results in suppression of c-myc expression and cessation of cell proliferation. The nuclear matrix (NM), a nuclear skeleton resistant to DNase I digestion and high salt extraction, is proposed to be involved in DNA replication, gene regulation, and the correct distribution of DNA at mitosis. We have previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
3
3
0
Order By: Relevance
“…The authors showed sequence retention in the nuclear matrix fraction, but ruled out p25 as a MAR-binding protein. 19 In the present study, we confirmed the existence of the MAR within a ClaI/EcoRI fragment containing the c-myc 3 0 UTR and demonstrated that the 22 bp BUR-like core sequence, highly homologous to the SATB1-binding site in the IgH gene, was located adjacent to, but not within the 172 bp DraI/DraI fragment (Figure 1). This 22 bp sequence was clearly making physical contact with MAR-binding proteins, that is, SATB1 in Jurkat cells 6 and Sox2 in NT2 cells, and, therefore, may be regarded as the true BUR element within the c-myc MAR.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…The authors showed sequence retention in the nuclear matrix fraction, but ruled out p25 as a MAR-binding protein. 19 In the present study, we confirmed the existence of the MAR within a ClaI/EcoRI fragment containing the c-myc 3 0 UTR and demonstrated that the 22 bp BUR-like core sequence, highly homologous to the SATB1-binding site in the IgH gene, was located adjacent to, but not within the 172 bp DraI/DraI fragment (Figure 1). This 22 bp sequence was clearly making physical contact with MAR-binding proteins, that is, SATB1 in Jurkat cells 6 and Sox2 in NT2 cells, and, therefore, may be regarded as the true BUR element within the c-myc MAR.…”
Section: Discussionsupporting
confidence: 72%
“…# X00364, UCSC Human genome version hg16) obtained via the UCSC Genome Browser. 25 The analysis confirmed the presence of a 370 bp S/MAR region located in the 3 0 UTR between nt 7366-7735, consistent with previous studies of Chou et al, 18,19 who reported the presence of a MAR at the 3 0 -end of the gene within a 1.4 kb ClaI and EcoRI restriction fragment (Figure 1). Furthermore, within this 370 bp S/MAR region, we identified a sequence (5 0 TTTTTTTCTA TTGTTTTTAGAA3 0 , nt 7627-7647) highly homologous to the well-characterized 25 bp BUR core element of the mouse IgH gene.…”
Section: Introductionsupporting
confidence: 80%
See 3 more Smart Citations